Perspective: The gap between intent and climate action in agriculture - Vyas, Shalika; Khatri-Chhetri, Arun; Aggarwal, Pramod K.; Thornton, Philip K.; Campbell, Bruce M. (Elsevier, 2022)
This paper presents a framework based on four dimensions—intent, need, scope and readiness for implementing adaptation and mitigation in agriculture.